1991
DOI: 10.1179/sur.1991.7.4.319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coatings on Rolling Contact Fatigue Behaviour of MSO Bearing Steel

Abstract: There is a continuing requirement for improved bearing performance for both commercial and military applications. Service temperatures are increasing steadily due to increased power requirements and corrosion of components remains a major concern as well, particularly for bearings in military systems. In our ongoing study, a number of different coatings were applied to VIM–VAR M50 bearing steel to improve both corrosion resistance and rolling contact fatigue behaviour. This report deals with coatings from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The 0.75 μm thick coating improved rolling contact FL while the 1.47 and 2.08 μm thick coatings showed worse rolling contact fatigue resistance. 39 Middleton et al 15 found that 1 µm thick TiN coatings on M50 steel improved the L 50 life nearly fourfold, while 0.25 µm thick coatings showed no improvement. Polonsky et al 23 found that the L 50 FL of M50 steel was increased by 2 to 3 times by TiN coatings with a optimum coating thickness of about 0.75 µm.…”
Section: Effects Of Coating Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…The 0.75 μm thick coating improved rolling contact FL while the 1.47 and 2.08 μm thick coatings showed worse rolling contact fatigue resistance. 39 Middleton et al 15 found that 1 µm thick TiN coatings on M50 steel improved the L 50 life nearly fourfold, while 0.25 µm thick coatings showed no improvement. Polonsky et al 23 found that the L 50 FL of M50 steel was increased by 2 to 3 times by TiN coatings with a optimum coating thickness of about 0.75 µm.…”
Section: Effects Of Coating Thicknessmentioning
confidence: 99%
“…13 The rolling contact FL of 1 µm thick TiN-coated M50 steel was improved nearly fourfold. 15 Polonsky et al 23 evaluated the performance of TiN coatings of different thicknesses. They found that the L 50 FL of M50 steel was increased by 2 to 3 times by TiN coatings with the optimum coating thickness of about 0.75 µm.…”
Section: Performance Of Pvd Coatings On Rolling Componentsmentioning
confidence: 99%
“…A further increase in need for high performance balls and roller bearing components that can withstand extreme applications has led to a growing interest in hard coatings for their better fatigue life and wear resistance. [9][10][11] In particular, hard TiN and TiC (N) coatings and also DLC films 12,13 have attracted and still attract much attention of manufacturers. Experiments conducted on compact materials showed that the hard coatings can effectively extend the fatigue life of steel bearings.…”
Section: Introductionmentioning
confidence: 99%
“…This work illustrates the need for improving the land wear resistance of the P675. Literature survey indicates that surface modification techniques, such as coatings [5][6][7], ion implantation [7,8], low plastic burnishing [9] and laser surface texturing [10] can be applied to enhance the wear resistance of the land surface.…”
Section: Introductionmentioning
confidence: 99%